2008
DOI: 10.1016/j.str.2008.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Staphylococcus aureus AgrA LytTR Domain Bound to DNA Reveals a Beta Fold with an Unusual Mode of Binding

Abstract: The LytTR domain is a DNA-binding motif found within the AlgR/AgrA/LytR family of transcription factors that regulate virulence factor and toxin gene expression in pathogenic bacteria. This previously uncharacterized domain lacks sequence similarity with proteins of known structure. The crystal structure of the DNA-binding domain of Staphylococcus aureus AgrA complexed with a DNA pentadecamer duplex has been determined at 1.6 A resolution. The structure establishes a 10-stranded beta fold for the LytTR domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
174
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(183 citation statements)
references
References 40 publications
5
174
0
2
Order By: Relevance
“…While the structure of AtcR has not yet been determined, threading of the AtcR sequence onto the AgrA:DNA complex structure suggests that AtcR and AgrA have similar structures (Miller et al 2014a;Sidote et al 2008). Ramachandran plotting provided strong support for the predicted AtcR structure as 89.36% of the residues were calculated to have favorable bond angles (Miller et al 2014a).…”
Section: Structural Modeling Of Atcrmentioning
confidence: 93%
See 4 more Smart Citations
“…While the structure of AtcR has not yet been determined, threading of the AtcR sequence onto the AgrA:DNA complex structure suggests that AtcR and AgrA have similar structures (Miller et al 2014a;Sidote et al 2008). Ramachandran plotting provided strong support for the predicted AtcR structure as 89.36% of the residues were calculated to have favorable bond angles (Miller et al 2014a).…”
Section: Structural Modeling Of Atcrmentioning
confidence: 93%
“…The predicted AtcR structural model suggests that the interaction of AtcR with DNA is also likely to be similar to that of AgrA with strong potential for residues within the loops of AtcR to insert into the major grooves of potential LytTR-DNA motifs. AgrA residues H169, N201, and R233 have been demonstrated to be in direct contact with DNA (Sidote et al 2008). Sequence alignment revealed that AtcR residues H157, R191, and R221 are positionally analogous to the AgrA-DNA contact residues.…”
Section: Structural Modeling Of Atcrmentioning
confidence: 99%
See 3 more Smart Citations